Per Enza Biagini - Brettoni, Augusta; Piazzesi, Sandro; PELLEGRINI, Ernestina; Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2016)
Studi per Enza Biagini ("Studies for Enza Biagini") collects essays on literary theory or comparative studies, analysing a single or multiple literatures, translations, poems, stories and comics. The result is a text of pleasant and agile reading. Generations of scholars intersect, who do not belong to any academic hierarchy, and who have shared over the decades the long history and the many fields of research of Enza Biagini, also revealing the methodological rigour and the almost boundless openness that has characterized her school. At the heart of the volume is the theory of literature with its concepts and tools of analysis belonging to the tradition of rhetoric, not to be understood here as the taxonomy of tropes and figures, but as the sum of living instances (linguistic, literary, philosophical, semiotic, ideological) which are the bearers of fundamental questions.